Floral Mass per Area and Water Maintenance Traits Are Correlated with Floral Longevity in Paphiopedilum (Orchidaceae) - Zhang, Feng-Ping; Yang, Ying-Jie; Yang, Qiu-Yun; Zhang, Wei; Brodribb, Tim J.; Hao, Guang-You; Hu, Hong; Zhang, Shi-Bao (Frontiers in Plant Science, 2017)
Floral longevity (FL) determines the balance between pollination success and flower maintenance. While a longer floral duration enhances the ability of plants to attract pollinators, it can be detrimental if it negatively affects overall plant fitness. Longer-lived leaves display a positive correlation with their dry mass per unit area, which influences leaf construction costs and physiological functions. However, little is known about the association among FL and floral dry mass per unit area (FMA) and water maintenance traits. We investigated whether increased FL might incur similar costs. Our assessment of 11 species of Paphiopedilum (slipper orchids) considered the impact of FMA and flower water-maintenance characteristics on FL. We found a positive relationship between FL and FMA. Floral longevity showed significant correlations with osmotic potential at the turgor loss and bulk modulus of elasticity but not with FA. Neither the size nor the mass per area was correlated between leaves and flowers, indicating that flower and leaf economic traits evolved independently. Therefore, our findings demonstrate a clear relationship between FL and the capacity to maintain water status in the flower. These economic constraints also indicate that extending the flower life span can have a high physiological cost in Paphiopedilum.